Life-long endurance running is associated with reduced glycation and mechanical stress in connective tissue - Couppé, Christian (Springer Netherlands, 2014)
Life-long regular endurance exercise is known to counteract the deterioration of cardiovascular and metabolic function and overall mortality. Yet it remains unknown if life-long regular endurance exercise can influence the connective tissue accumulation of advanced glycation endproducts (AGEs) that is associated with aging and lifestyle-related diseases. We therefore examined two groups of healthy elderly men: 15 master athletes (64 ± 4 years) who had been engaged in life-long endurance running and 12 old untrained (66 ± 4 years) together with two groups of healthy young men; ten young athletes matched for running distance (26 ± 4 years), and 12 young untrained (24 ± 3 years). AGE cross-links (pentosidine) of the patellar tendon were measured biochemically, and in the skin, it was assessed by a fluorometric method. In addition, we determined mechanical properties and microstructure of the patellar tendon. Life-long regular endurance runners (master athletes) had a 21 % lower AGE cross-link density compared to old untrained. Furthermore, both master athletes and young athletes displayed a thicker patellar tendon. These cross-sectional data suggest that life-long regular endurance running can partly counteract the aging process in connective tissue by reducing age-related accumulation of AGEs. This may not only benefit skin and tendon but also other long-lived protein tissues in the body. Furthermore, it appears that endurance running yields tendon tissue hypertrophy that may serve to lower the stress on the tendon and thereby reduce the risk of injury.